Koala : a first field guide to the cuddly marsupial from Australia - Daniels, Christopher B.; Lock, Marianne (2023)
"A beautifully illustrated guide to koalas for kids written by expert Chris Daniels"--
Includes index.
Ages 6-8
Grades 2-3
Keywords: Koala -- Juvenile literature